Bivariate Pareto–Feller distribution based on appell hypergeometric function - Caamaño Carrillo, Christian.; Bevilacqua, Moreno; Zamudio Monserratt, Michael.; Contreras Reyes, Javier Esteban. (MDPI, 2024)
The Pareto-Feller distribution has been widely used across various disciplines to model "heavy-tailed" phenomena, where extreme events such as high incomes or large losses are of interest. In this paper, we present a new bivariate distribution based on the Appell hypergeometric function with marginal Pareto-Feller distributions obtained from two independent gamma random variables. The proposed distribution has the beta prime marginal distributions as special case, which were obtained using a Kibble-type bivariate gamma distribution, and the stochastic representation was obtained by the quotient of a scale mixture of two gamma random variables. This result can be viewed as a generalization of the standard bivariate beta I (or inverted bivariate beta distribution). Moreover, the obtained bivariate density is based on two confluent hypergeometric functions. Then, we derive the probability distribution function, the cumulative distribution function, the moment-generating function, the characteristic function, the approximated differential entropy, and the approximated mutual information index. Based on numerical examples, the exact and approximated expressions are shown.
Keywords: Generalized gamma distribution; Beta prime marginal distributions; Moment generation function; Entropía